2019
DOI: 10.15625/2525-2518/57/1/12682
|View full text |Cite
|
Sign up to set email alerts
|

PREPARATION AND FTIR STUDIES OF PMMA/PVC POLYMER BLENDS, PVC-g-PMMA GRAFT COPOLYMERS AND EVALUATING GRAFT CONTENT

Abstract: This study presents the qualitative and quantitative analyses of Fourier Transform Infrared (FTIR) spectra of poly(methyl methacrylate)/poly(vinyl chloride) blends (PMMA/PVC), as well as PVC-g-PMMA graft copolymers. Graft copolymerizations of methyl mathacrylate (MMA) onto PVC macromolecules were carried out mixture of cyclohexanone/N,N-dimethylformamide as solvents, dibenzoyl peroxide as initiator and nitrogen medium. FTIR spectra of PMMA/PVC blends showed that there were molecular interactions between C=O gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Referring to our previous study, three ν(C-Cl) vibration modes of pure PVC were reported, appearing at 692, 636 and 614 cm -1 [27]. In this study, only two vibration modes of ν(C-Cl) at 637 and 616 cm -1 in spectra of P200 sample are observed, the next peak (at 651 cm -1 ) is attributed to aromatic ring bending (r ing ) of DOP.…”
Section: The Ftir Spectra Of Plasticized Pmma/pvc/mg(clo 4 ) 2 Electrsupporting
confidence: 68%
“…Referring to our previous study, three ν(C-Cl) vibration modes of pure PVC were reported, appearing at 692, 636 and 614 cm -1 [27]. In this study, only two vibration modes of ν(C-Cl) at 637 and 616 cm -1 in spectra of P200 sample are observed, the next peak (at 651 cm -1 ) is attributed to aromatic ring bending (r ing ) of DOP.…”
Section: The Ftir Spectra Of Plasticized Pmma/pvc/mg(clo 4 ) 2 Electrsupporting
confidence: 68%
“…Figure 1 displays the FTIR spectra of the raw materials and synthesized samples. Referred to previous studies [22], it is very easy to assigned all absorption peaks for specific groups of PMMA (Figure 1 Advances in Polymer Technology new peaks attributed to the presence of plasticizers, the peaks at 1805 cm -1 and 1732 cm -1 can be assigned for C=O stretching vibrations (ν) of the PC plasticizer and PMMA, and the doublet at 1600 and 1580 cm -1 is assigned for aromatic ring of the DOP plasticizer (Table 2 It can be seen that there are wrinkles on the surfaces of two kinds of samples (undoped and doped with magnesium salt), which are caused by the high flexibility of the films containing high plasticizer content. It was reported that PMMA/PVC blend films have craters or islands due to the immiscibility of ethylene/propylene carbonate plasticizer with PVC, which caused the separation of the PVC-rich phase and plasticizer-rich phase [26].…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of Electrolyte Films. Graft copolymer of PVC-g-PMMA (labeled as PVCg) with the PMMA graft content of 20.3 wt% had been prepared as stated in the previous study [22]. As similarly, the weight ratio of PVC : PMMA was kept as 1 : 1 in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the bands at 1389, 1063, 991, 963, 724, 750 cm −1 are characterized of the asymmetric bending vibrations of (C−CH 3 ), C−O−C stretching vibration, −OCH 3 symmetric stretching and CH 3 rocking, CH 2 long chain in 1H and MM, respectively [10,59–64] …”
Section: Resultsmentioning
confidence: 99%